The Catholic Experience in America From Orestes Brownson to the Bozells: A Precedent for Muslims? (American Journal of Islam and Society, 2025)
Muslim Americans confront the challenges of adapting to a liberal culture that is both formally tolerant and ideologically compelling; a culture often understood as growing out of the individualistic and anti-authoritarian features of the Protestant Reformation. Scholars such as Harold Bloom and Alan Wolfe have argued that due to its appeal, this dominant culture—what may be called the American creed—transforms all other faiths into variants of itself. They predict that a similar liberalizing assimilation will take place with Islam. In order to assess the validity of this prediction and its implications, this article looks at the experience of another religion that also came to America resistant to the individualistic focus of the American creed. It does so by tracing the evolution of American Catholicism beginning with perhaps its most influential exponent, the nineteenth-century convert Orestes Brownson. After reviewing—through demographic and public opinion data as well as the analyses of some leading contemporary Catholic thinkers—how successfully Catholicism has maintained its identity in the American context since Brownson’s time, the article concludes by considering the implications for Muslim Americans.